A diamond in the rough : J.M. Huber and the PATH business - Ward, John L., (SAGE Knowledge. Cases., 2017)
In late 2011, Jerry Bertram, vice president and general manager of the fire retardant additives business of Huber Engineered Materials (HEM), a division of family-owned J. M. Huber Corporation, was preparing to present the potential acquisition of the precipitated alumina trihydrate (PATH) business to the environment, health, and safety committee of Huber's corporate board. He had convinced HEM's leadership of PATH's strategic value to their business and the urgency of the acquisition based on PATH's parent company's movement into Chapter 11 bankruptcy and its plans to close the PATH plant.Winning board approval posed a major challenge. It was unclear whether the plant would remain operational, because HEM would have to enter a shared-services arrangement with PATH's parent company, which continued to use the site. In addition, acquiring PATH would mean integrating its specialized, unionized labor force into Huber, which had very few union workers. Finally, early due diligence had revealed tens of millions of dollars of potential environmental risk on the site. The last issue was particularly critical, given Huber's generations-long history of respect for the environment, and its executives' and directors' reluctance to take on any business with excessive environmental risk.This case illustrates in depth the family business values that can promote consideration of an ostensibly unconventional and risky strategic move, and enable executives to push for approval of the same, as backed by comprehensive risk assessment and mitigation plans.